Odpowiedzi

Najlepsza Odpowiedź!
  • Roma
  • Community Manager
2010-02-22T11:13:15+01:00
1. 4(2a + 3b - 4c) = 8a + 12b - 16c

2. -2(5a - b +2c) = - 10a + 2b - 4c

3. -(x + 2y - 3z + 4) - (3x - 4y +5z - 2) + (4y - y +5z - 1) = - x - 2y + 3z - 4 - 3x + 4y - 5z + 2 + 4y - y + 5z - 1 = - 4x + 5y + 3z - 3

4. 2(3x +2y - 4z +5) + 3(5x - 8y +2z - 1) + (4x - 2y + 7z +8) = 6x + 4y - 8z + 10 + 15x - 24y + 6z - 3 + 4x - 2y + 7z + 8 = 25x - 22y + 5z + 15
8 5 8
2010-02-22T13:41:46+01:00
1.
4(2a + 3b - 4c) =
8a+12b-16c

2.
-2(5a - b +2c) =
-10a+2b-4c

3.
-(x + 2y - 3z + 4) - (3x - 4y +5z - 2) + (4y - y +5z - 1) =
-x-2y+3z-4-3x+4y-5z+2+4y-y+5z-1 =
-4x+5y+3z-3

4.
2(3x +2y - 4z +5) + 3(5x - 8y +2z - 1) + (4x - 2y + 7z +8) =
6x+4y-8z+10+15x-24y+6z-3+4x-2y+7z+8 =
25x-22y+5z+15
6 4 6